2010
DOI: 10.1093/nar/gkq214
|View full text |Cite
|
Sign up to set email alerts
|

CdnL, a member of the large CarD-like family of bacterial proteins, is vital for Myxococcus xanthus and differs functionally from the global transcriptional regulator CarD

Abstract: CarD, a global transcriptional regulator in Myxococcus xanthus, interacts with CarG via CarDNter, its N-terminal domain, and with DNA via a eukaryotic HMGA-type C-terminal domain. Genomic analysis reveals a large number of standalone proteins resembling CarDNter. These constitute, together with the RNA polymerase (RNAP) interacting domain, RID, of transcription–repair coupling factors, the CarD_TRCF protein family. We show that one such CarDNter-like protein, M. xanthus CdnL, cannot functionally substitute Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(117 citation statements)
references
References 48 publications
(89 reference statements)
5
112
0
Order By: Relevance
“…7). The only interaction observed by the two-hybrid analysis was that of CarD with the RNAP ␤ subunit, concordant with our earlier data using specific domains of either protein (16). Thus, CarD physically associates with RNAP, and this appears to be achieved via the ␤ subunit of RNAP, without involving the other RNAP core subunits or CarQ.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…7). The only interaction observed by the two-hybrid analysis was that of CarD with the RNAP ␤ subunit, concordant with our earlier data using specific domains of either protein (16). Thus, CarD physically associates with RNAP, and this appears to be achieved via the ␤ subunit of RNAP, without involving the other RNAP core subunits or CarQ.…”
Section: Resultssupporting
confidence: 91%
“…If this were so, stable or transient interactions could occur between RNAP and CarD. Two-hybrid analysis had actually indicated that the CarD N-terminal domain can interact with a fragment from the N-terminal region of the M. xanthus RNAP ␤ subunit (16). However, it remained to be validated if this physical interaction persisted for the full-length forms of CarD and RNAP ␤.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations